Nutritional Status of Children Seeking Medical Treatment in a Rural Hospital in Ilam District, Nepal - Paneru, C; George, SM (Journal of Nepal Paediatric Society, 2015)
Introduction: Childhood malnutrition is a leading cause of mortality and morbidity in children under five years in Nepal. There is evidence to show that childhood malnutrition varies from region to region, within Nepal. But there is no data available about nutritional status of children in the 75 districts in Nepal. The aim of this study was to evaluate the nutritional status of children less than five years of age in Ilam district. Material and Methods: We analysed the anthropometric data for the children of Ilam district who visited Dr. Megh Bahadur Parajuli Community Hospital in Ilam district. Results: Our data showed that 15.7% of girls and 21.2% of boys under-five years suffered from moderate malnutrition. Severe malnutrition was present in 6.7% of girls and 9.6% of boys. Stunting was seen in 32.6% girls and 30.16% boys. Moderate stunting was present in 19.6% of girls and 19% of boys; while severe stunting was present in 11% of the boys and 13% of the girls. Conclusion: Our data shows that stunting among under-fives in Ilam is less as compared to that reported for Nepal, but underweight is comparable to the national data. However, a systematic study needs to be carried out in Ilam before drawing firm conclusions. J Nepal Paediatr Soc 2014;34(3):207-215-220 DOI: http://dx.doi.org/10.3126/jnps.v34i3.10737